Comparative assessment of single axis manual solar PV trackers: A case study for agricultural applications - Jad Atallah; Pierre Rahme; Jimmy S. Issa (Energy Conversion and Management: X)
Harnessing solar energy through photovoltaic (PV) systems has become crucial due to the global need for sustainable energy solutions. Agricultural projects are often conducted in remote areas lacking direct access to the power grid. This study evaluates four solar system configurations for irrigation. The first is a fixed-panel system with panels oriented south at an optimized tilt angle. The second and third systems involve manual adjustment, requiring one or two rotations per day to enhance solar tracking. The fourth configuration is a dual-axis tracking system, which continuously tracks the sun in real-time. The case study, conducted over six months (May to October) in northern Lebanon, utilized hourly solar irradiance data from an on-site pyranometer to determine optimal tilt angles for the fixed and manually adjusted systems. Solar irradiation received by each configuration was then calculated and compared. Results show the dual-axis system performed best, capturing 38% more solar energy than the fixed system. Manually adjusted systems also improved efficiency, with one-time daily rotation increasing energy capture by 23% and two-time daily rotation by 28%. Although the dual-axis system achieves maximum performance, manually adjusted systems provide a cost-effective alternative with significant efficiency gains and lower installation and maintenance expenses.